1998
DOI: 10.1099/00222615-47-7-615
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two serological methods and a polymerase chain reaction-enzyme immunoassay for the diagnosis of acute respiratory infections with Chlamydia pneumoniae in adults

Abstract: Chlamydia pneumoniae is a common respiratory tract pathogen. Serological methods currently used for the diagnosis of C. pneumoniae infection lack specificity, give ambiguous results from a single serum sample and often provide only a retrospective diagnosis. A prospective study was undertaken to assess whether PCR could be a useful addition to the serological techniques routinely practised for diagnosis. This study investigated 68 adult patients with a diagnosis of acute respiratory infection. Acute and conval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Petitjean et al. (26) tested 25 viral and bacterial species in this PCR assay and no hybridization was seen.…”
Section: Discussionmentioning
confidence: 99%
“…Petitjean et al. (26) tested 25 viral and bacterial species in this PCR assay and no hybridization was seen.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of these cases as true C. pneumoniaerelated episodes would have increased the number of cases of chlamydia pneumonia from 11 to 56 and the percentage of cases of mixed pneumonia to 8%. Because the clinical signif- icance of a single high titer of IgG to C. pneumoniae is still unclear, we decided to consider this diagnosis only for cases in patients in whom seroconversion was evident [19,[22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported rather good agreement between different serological tests and detection of C. pneumoniae by PCR or culture (22). A poor correlation was found between rEIA and PCR in a third study, but only a few positive cases were detected (20).…”
Section: Discussionmentioning
confidence: 99%